The effect of gamma radiation on the structure of graphene oxide and graphene oxide functionalized with amino-PEG (Brazilian Journal of Radiation Sciences (BJRS), 2019)
ABSTRACT Covalent functionalization of graphene oxide (GO) with polyethylene glycol (PEG) has been widely used in drug delivery systems. This nanocomposite exhibits excellent stability in the presence of high concentrations of salts and proteins and shows low toxicity compared to its raw form. However, must be sterilized prior to use in medical devices, and the gamma irradiation shows a promising option for this purpose. Sterilization by ionizing energy through gamma rays, generated by Cobalt-60 self-disintegration, consists in exposing the materials to short electromagnetic waves. The irradiation process provides substantial advantages when compared to thermal and chemical processes such as more precise control of the process, lower energy consumption, and less environmental pollution. In this work the effects of gamma radiation on GO and GO functionalized com Amino-PEG (GO-PEG-NH2) irradiated with doses (15, 25, 35 and 50 kGy) that have been used to sterilize medical devices and at rate dose 7.3 kGy.h-1 were evaluated. The analyses were performed by Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy. The results showed that gamma radiation up to 50 kGy did  not cause any defects on the nanomaterials.